ONSA:optimal non-uniformly statistic-source anonymity protocol in WSN - Xiao-guang NIU; Chuan-bo WEI; Wei-jiang FENG; Guo-jun PENG; Huan-guo ZHANG (Tongxin xuebao)
According to the characteristics of hierarchical event source-location privacy (SLP) in wireless sensor networks (WSN).Firstly,the effect of the cluster size and the statistical property of fake packet injection on the privacy,latency and network traffic were analyzed.Then,an optimal non-uniformly statistic-source anonymity protocol (ONSA)was proposed to achieve source anonymity and reduce the network traffic.ONSA is designed to achieve a tradeoff between network traffic and real event report latency through adjusting the transmission rate and the radius of non-uniform clusters.The simulation results demonstrate that ONSA significantly reduces the network traffic while providing source anonymity and meeting the system requirement of the delay.